2012
DOI: 10.1074/jbc.m111.305938
|View full text |Cite
|
Sign up to set email alerts
|

Torque Generation and Utilization in Motor Enzyme F0F1-ATP Synthase

Abstract: Background: ATP synthase (F 0 F 1 ) is a rotary motor enzyme. Results: F 1 with a short-sized helix-1 in ␤ subunit rotates with half of the normal torque and supports reduced ATP synthesis activity. Conclusion: Helix-1 acts as a "pushrod" to generate torque, and torque-reduced F 0 F 1 retains the catalytic ability of ATP synthesis. Significance: Generation and utilization of the torque are crucial for motor enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Recent single-molecule studies have revealed that the C -terminal region of the β subunit shows a large-scale conformational change at around 0°533, which contributes to generating half of the rotational torque, that is, approximately 20 pN·nm rad −1 3435. Our experimental results suggest that the TS reaction contributes greatly to torque generation at around 0°.…”
Section: Discussionmentioning
confidence: 49%
“…Recent single-molecule studies have revealed that the C -terminal region of the β subunit shows a large-scale conformational change at around 0°533, which contributes to generating half of the rotational torque, that is, approximately 20 pN·nm rad −1 3435. Our experimental results suggest that the TS reaction contributes greatly to torque generation at around 0°.…”
Section: Discussionmentioning
confidence: 49%
“…However, the mechanism contributing to the energy deficit remains unclear owing to the diversity of energy regulatory elements and complexity of energy production, transfer and control. Moreover, a growing body of evidence indicates that cellular energy levels are closely related to the activity, transcription and translation of certain regulatory elements [15-18]. Among these regulatory elements, proteins that synthesize (ATP synthase), dissipate (alternative oxidase, AOX; and mitochondrial inner membrane uncoupling proteins, UCP), transport [adenosine diphosphate (ADP)/ATP carrier, AAC] and regulate (sucrose non-fermenting-1-related kinase, SnRK) ATP have attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…The 22 residues of the N-terminal helix and the 43 residues of the C-terminal helix in the γ subunit are deleted. c The positions of deletion in the HTH structure are shown in red (Usukura et al 2012). d All residues of the HTH in contact with the γ subunit are substituted with glycine or alanine ( red region ) (Tanigawara et al 2012) …”
Section: Robustnessmentioning
confidence: 99%
“…The helix-turn-helix (HTH) structure of the β subunits forming the main interface of the stator orifice was investigated (Usukura et al 2012). Figure 5a highlights the HTH structure in blue.…”
Section: Robustnessmentioning
confidence: 99%
See 1 more Smart Citation